2021
DOI: 10.1002/rth2.12571
|View full text |Cite
|
Sign up to set email alerts
|

Emicizumab initiation and bleeding outcomes in people with hemophilia A with and without inhibitors: A single‐center report

Abstract: Background Emicizumab, a bispecific antibody factor VIII mimetic, is approved for prophylaxis in hemophilia, and has different risks and side effects compared to factor VIII products. Objective To better understand the early impact of emicizumab on our patients at the University of Colorado Hemophilia and Thrombosis Center (UCHTC), we evaluated adverse reactions, factor prophylaxis overlap, and bleeding rates after starting emicizumab through a quality improvement proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Beyond the clinical trials, emicizumab safety has been documented in multiple real‐world experiences in patients with and without inhibitors 13–19 . In these studies, the emicizumab safety profile was similar to that seen in clinical trials.…”
Section: Emicizumab Rolloutmentioning
confidence: 82%
See 3 more Smart Citations
“…Beyond the clinical trials, emicizumab safety has been documented in multiple real‐world experiences in patients with and without inhibitors 13–19 . In these studies, the emicizumab safety profile was similar to that seen in clinical trials.…”
Section: Emicizumab Rolloutmentioning
confidence: 82%
“…Yet, paediatric data and data regarding emicizumab's potential use in PUPs were not specified. 13 The most extensive prospective paediatric study reported to date is the Israeli cohort that sought to evaluate safety, efficacy, and laboratory monitoring of emicizumab prophylaxis in a cohort of 40 children with severe HA, including 22 non-inhibitor patients and nine infants younger than one year. Bleeding, trauma, adverse events, and surgeries were documented during a median follow-up of 45 weeks.…”
Section: Update On Paediatric Clinical Studies and The Real-world Exp...mentioning
confidence: 99%
See 2 more Smart Citations
“…The ABR reported in our cohort is comparable to the ABR of previous study populations on emicizumab. 22,23 …”
Section: Discussionmentioning
confidence: 99%